Effect of L-carnitine on starter pig performance and fat utilization - Weeden, T.L.; Hansen, J.A.; Fitzner, G.E.; Li, D.F.; Blum, S.A.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred early-weaned pigs with average initial weights of 12.3 and 13.2 lb, respectively, were utilized in two 5-wk experiments to determine the effect of L-carnitine on growth Performance. Diets contained 20% dried skim and 20% dried whey in phase 1 ( 0 to 14 d) for both experiments and 20 and 10% dried whey, respectively for experiments 1 and 2 in phase 2 (15 to 35 d). In experiment 1, L-carnitine at levels of 0, 500, and 1000 ppm was combined with 0 or 10% soybean oil in phase 1, levels were reduced by 50% in phase 2 to 0, 250, and 500 ppm L-carnitine and 0 or 5% soybean oil. There was no improvement in pig performance from addition of either L-carnitine or soybean oil in phase 1. In phase 2 and for the cumulative 5 wk experiment, soybean oil addition improved average daily gain (ADG) but had no effect on feed intake (Fl) or feed/gain (F/G). Feed efficiency was improved linearly as the level of L-carnitine was increased in phase 2, however, there was no effect on ADG or Fl. In experiment 2, L-carnitine levels in phase 1 were 0 and 1000 ppm, combined with levels of 0, 250, and 500 ppm in phase 2. Addition of L-carnitine improved ADG and increased FI, but had no effect on F/G the first 2 wk postweaning. In phase 2, increasing the level of L-carnitine resulted in improved F/G. Feed intake was decreased as L-carnitine level increased. There was no effect on ADG in phase 2 or during the cumulative 5 wk experiment from level of L-carnitine fed. Feed efficiency improved and FI decreased over the 5 wk trial as the level of L-carnitine increased. Based on the results of these experiments, addition of L-carnitine shows the potential to improve F/G by 11 to 16% in phase 2 and 7 to 9 % for the overall starter phase.
Keywords: Swine; Starter; Performance; Carnitine; Soybean oil